2016
DOI: 10.1152/ajpcell.00350.2015
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic acid attenuates cAMP-dependent Cl secretion in human colonic epithelial T84 cells

Abstract: Bile acids (BAs) play a complex role in colonic fluid secretion. We showed that dihydroxy BAs, but not the monohydroxy BA lithocholic acid (LCA), stimulate Cl Ϫ secretion in human colonic T84 cells (Ao M, Sarathy J, Domingue J, Alrefai WA, Rao MC. Am J Physiol Cell Physiol 305: C447-C456, 2013). In this study, we explored the effect of LCA on the action of other secretagogues in T84 cells. While LCA (50 M, 15 min) drastically (Ͼ90%) inhibited FSK-stimulated short-circuit current (Isc), it did not alter carbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…We and others have shown that LCA does not activate Cl − secretion, but attenuates the prosecretory effects of cAMP‐dependent agents in T84 cells (Ao et al. ).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…We and others have shown that LCA does not activate Cl − secretion, but attenuates the prosecretory effects of cAMP‐dependent agents in T84 cells (Ao et al. ).…”
Section: Introductionmentioning
confidence: 80%
“…We have reported that these cells were female as determined by RT‐PCR amplification of the amelogenin gene (Ao et al. ). Cells, between passages 39 and 50, were incubated in a humidified atmosphere of 5% CO 2 at 37°C and grown in Transwells until transepithelial resistance (TER) reached 1000 Ω cm 2 (generally 2–3 weeks).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 This discrepancy may be due to differences in agonist action on GpBAR1. Ursodeoxycholic acid and lithocholic acid attenuate colonic epithelial secretory function 22,23 In contrast, DCA activates ion channels in colonocytes and acts on non-epithelial cells to activate chloride secretion indirectly. 17 Furthermore, pretreatment with TTX changed the secretory responses to DCA, confirming that the nervous system is associated with secretion induced by DCA.…”
Section: Discussionmentioning
confidence: 99%